PENGARUH KERAGAMAN PRODUK BROWNIES KUKUS TERHADAP LOYALITAS KONSUMEN (Studi Kasus Pada CV. Amanda Jalan Rancabolang 29 Bandung) - Harun Heri Trismiyanto (Program Studi Manajemen, Universitas Al Ghifari, 2020)
This study aims to determine how much influence the diversity of products on consumer loyalty, and the sample of respondents is the customer who made Amanda Brownies Road Ranca Bolang no. 29 Bandung. Data analysis phase begins by gathering data by distributing questionnaires to the respondents of 60, after the data collected and processed using SPSS 17.0. To avoid any mistakes prior to the discussion, the validity and reliability testing performed on each question of each variable, where results of testing the validity greater than 0300, which means all of the questions indicates a valid result, and for the reliability test results greater than 0700, which showed reliable results.The method used in this study is the verification method and descriptive method, which verifikatif methods used to verify the hypothesis, while the descriptive method is used to explain, describe the situation, circumstances and events of the object of research to test hypotheses using statistical calculations. Testing the hypothesis in this study using the Simple Linear Regression analysis, and results obtained showed that significant diversity of products that affect consumer loyalty by 60.80%. The results obtained from the test results significantly and the balance of 30.20% are factors beyond this study that affect customer loyalty.Based on the results of hypothesis testing, means that consumers' assessment of the diversity of Amanda Brownies brownies products showed that the average consumer ratings Amanda Brownies included in the category of